Total Arterial Myocardial Revascularization on a Beating Heart in Patients with Atherosclerotic Damage of Coronary Vessels - Gabriyelyan, A.; Mazur, A.; Beleyovych, V.; Domansky, T.; Chaikovska, S. (Ukrainian Journal of Cardiovascular Surgery, 2020)
Introduction. One of the main unresolved problems in coronary surgery has been the search for an “ideal” graft for coronary artery bypass surgery. Surgical procedures with the use of artificial circulation can lead to high incidence of postoperative complications compared to operations on a beating heart. The aim. To study the results of total arterial myocardial revascularization on a beating heart and to evaluate the medium-term outcomes in patients with coronary heart disease. Materials and methods. Ninety eight patients with coronary heart disease were treated from 2009 to 2013. The patients underwent total arterial myocardial revascularization on a beating heart using only arterial grafts: those obtained from internal thoracic artery, radial artery, and right gastroepiploic artery. Results and discussion. No deaths were observed in the postoperative period. In 91 (92.8%) patients, the postoperative period was uneventful. After 5 years of follow-up, clinical and non-invasive methods of examination revealed no coronary circulation disorders. Conclusions. Our clinical experience showed promising short- and medium-term results. The technique of total arterial myocardial revascularization on a beating heart is a good alternative to operations performed under the condition of artificial circulation.